Enhancing Leadership in the South African Police Service: Utilising the Opportunities of Advancements - (:unkn) unknown (My University, 2025)
The objective of this study is to evaluate and recommend improvements to the South African Police Service (SAPS) promotion process to bolster leadership capability, enhance succession planning, and ensure the selection of the most suitable individuals for executive positions. Primary Subjects: The study examines the existing SAPS promotion and assessment processes, evaluates the accessibility and efficacy of leadership development programs, identifies preferred leadership styles, and analyses the influence of the promotion process on organisational leadership. Principal Arguments/Conclusions: The existing SAPS promotion methods, which predominantly depend on written assessments, exhibit possible validity concerns in forecasting leadership capability. A perceived deficiency exists in accessible and pertinent leadership development programs, with a necessity to synchronise promotion procedures with preferred leadership styles, including ethical, transformational, and strategic leadership. It is essential to address diversity and inclusivity within leadership positions.
Keywords: African Research